Analisis Resepsi Audiens terhadap Serial Edutainment Academy of Champions yang Ditayangkan pada Channel YouTube Ruangguru (Riwayat: Educational Journal of History and Humanities, 2026)
This study departs from the phenomenon of digitization in various aspects, including education. An example of this is the establishment of the online learning platform Ruangguru. As a way to increase public interest, Ruangguru created a new strategy by producing an edutainment program called Academy of Champions. This study aims to analyze how audiences interpret the content of the Academy of Champions series broadcast on the Ruangguru YouTube channel. Using a qualitative approach with Stuart Hall's reception analysis method, this study classifies audience responses into three categories of interpretation: dominant-hegemonic position, negotiated position, and oppositional position. Data were collected through in-depth interviews with research subjects, who were students from SMA Negeri 10 Samarinda. The results of the analysis show that most informants are in a dominant-hegemonic position, whose assessments are in line with the main discourse of the Academy of Champions because the series successfully presents representations of high-achieving students who can be a source of inspiration and motivation for learning. Meanwhile, informants in a negotiating position accept part of the main discourse of the program, but adjust the meaning based on their respective interests and learning style preferences. This study shows that the interpretation of the program's message is diverse and influenced by personal experiences, motivations, learning preferences, and interests in entertainment.